(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
In today’s fast developed century chefs need some imagination and innovation to attract and catch customers. For this of course fusion cuisine can be the best approach by mixing some different cooking methods of various nations.